2008
DOI: 10.1074/mcp.m700137-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variation of the Platelet Proteome in the Elderly Population and Its Implication for Biomarker Research

Abstract: Knowledge about the extent of total variation experienced between samples from different individuals is of great importance for the design of not only proteomics but every clinical study. This variation defines the smallest statistically significant detectable signal difference when comparing two groups of individuals. We isolated platelets from 20 healthy human volunteers aged 56 -100 years because this age group is most commonly encountered in the clinics. We determined the technical and total variation expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 32 publications
4
53
0
4
Order By: Relevance
“…From our quantitative MS data, we could furthermore deduce that, using our reproducible isolation procedure, ≈80% of the platelet proteome showed only minor inter-and intradonor variation and were stable (1) between 4 healthy donors and (2) between blood donations of 1 donor over time (≈3 weeks). This was in good agreement with 2-DE derived data from Winkler et al, 46 who found a coefficient of variation of 18% based on 500 spots reproducibly found in platelets from healthy donors. In our study, the calculated amount of the 2 most prominent plasma proteins, serum albumin and transthyretin, allowed measurement of the degree of plasma contamination, which is inevitable because of the sponge-like structure of the platelet open canalicular system.…”
Section: Quantitative Human Platelet Proteomesupporting
confidence: 81%
See 2 more Smart Citations
“…From our quantitative MS data, we could furthermore deduce that, using our reproducible isolation procedure, ≈80% of the platelet proteome showed only minor inter-and intradonor variation and were stable (1) between 4 healthy donors and (2) between blood donations of 1 donor over time (≈3 weeks). This was in good agreement with 2-DE derived data from Winkler et al, 46 who found a coefficient of variation of 18% based on 500 spots reproducibly found in platelets from healthy donors. In our study, the calculated amount of the 2 most prominent plasma proteins, serum albumin and transthyretin, allowed measurement of the degree of plasma contamination, which is inevitable because of the sponge-like structure of the platelet open canalicular system.…”
Section: Quantitative Human Platelet Proteomesupporting
confidence: 81%
“…These require state-of-the-art equipment and either the usage of costly stable isotope labeling techniques which allow multiplexing of ≤10 samples to save time 50,51 or the successive analysis of single samples by label-free quantification strategies to characterize larger cohorts (Text Box 1). In the past few years, 2-DE was preferably used for disease-driven platelet proteomics, 46,52,53 but, as mentioned above, this technique has limitations when compared with gel-free LC-MS-based proteomics (Table I in the online Data Supplement).…”
Section: Text Box 1 Liquid Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…В работе по изучению вариабельности протеома тромбоцитов, выполненной Winkler с соавт., было также продемонстрировано, что отличия между индивидуумами значительно выше изменчивости, наблюдаемой при анализе нескольких образцов одного и того же испытуемого, полученных в разное время [47].…”
Section: * -адресат для перепискиunclassified
“…По данным Winkler с соавт., коэффициенты вариации 10 мажорных белков плазмы крови находятся в диапазоне от 9 до 41%. Так, коэффициент вариации альбумина составляет 9%, иммуноглобулина G -20%, трансферрина -14%, гаптоглобина -41%, комплемента С3с -17%, a-1 кислого гликопротеина -21%, a 2 -макроглобулина -20% [47]. Анализ низкомолекулярного субпротеома здоровых лиц также позволил выявить компоненты, характеризующиеся высокой и низкой индивидуальной вариабельностью.…”
Section: таблица 1 результаты вариабельности некоторых белков здоровunclassified